(untitled) (World Bulletin of Public Health, 2024)
Food allergy in children is a complex of symptoms arising in the process of inadequate immunological reaction of the organism to certain foods or their individual components. The disease is accompanied by a number of signs from the respiratory system, gastrointestinal tract, as well as skin and respiratory phenomena. Diagnosis, prevention and treatment of food allergy in children of different ages are carried out by allergists with the participation of dermatologists, infectious disease specialists, endocrinologists and other narrow specialists